From Mass to Universal Education - Benveniste, G. author. aut Link
XVIII, 126 p.
Keywords: precise, appeared until the recent crisis - to many Americans from the East of America's America, as the whole of America seemed to Europeans of a century ago: extreme and strange, full of violent contrasts, contradictory, over-advanced, neo primitive and savage, a land where everything is possible, the hippies and the religious-political fundamentalism of the Orange County, Marcuse, Angela Davis and Norman Brown, Esalen, the new consciousness. Alan Watts and Carlos Castaneda, as well as Patricia Hearst and the Sym bionese Liberation Army, Richard Nixon and his men, the Satan religion, outrageous crimes such as that of the Manson "family" and incredibly scan dalous business deals. For better or worse, California appears as a sort of preview of the European society of the future: the land of the Western World with the greatest immigration and population growth, with enormous cities which in the textbooks of your childhood were hardly even mentioned, e.g. Los Angeles, or were not mentioned at all, as in the case of San Diego and San Jose, a considerable urban development which has taken place almost overnight.